Etnicki cisto . Ethnically Clean. War Criminal: Dusan Boljevic - Matić, Veran; Baljak, Janko (Yugoslavia, 1997)
Soros Documentary Fund Dusan Boljevic, a member of the Serb rebel forces, killed 18 of his neighbours of Croatian and Hungarian nationality in 1991. Allegedly, he drank coffee with them and then killed them in cold blood. Long before the establishment of the Hague Tribunal, the Serbs tried him for war crimes against civilian population. The trial was held in the Republic of Serb Krayina (now Croatia) during war in that region. This film presents war criminals Dusan Boljevic and his wife Jagoda, three years after these crimes.